Faide indiane e allarmismi lombardi. La mediatizzazione del conflitto ‘etnico’ e la sua eco sulla quotidiana convivenza migranti/autoctoni - Sara Bonfanti (EtnoAntropologia)
Drawing from my research on Panjabi diasporas in Lombardy, I discuss the media hype which followed the accidental murder of an Italian lady doctor occurred in Bergamo in 2013, during a brawl among Panjabi family clans.